Functional Outcome in management of distal radius Giant Cell Tumour through En-Bloc Resection and Reconstruction with Ipsilateral Non-Vascularized Fibular Graft - D A.K.Prabhakaran,; Dr.Yeshwanth Subash, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Giant cell tumors (GCT) of the distal radius pose a significant challenge in management due to their unique clinical characteristics and the complexity of the distal radius region. This study addresses the multifaceted challenges by exploring the outcomes of en bloc resection and reconstruction with ipsilateral non-vascularized fibular graft. The distal radius's impact on wrist joint functionality, the late presentation of cases, and the imperative goals of complete excision and functional restoration necessitate innovative surgical approaches. Materials and Methods: A retrospective and prospective analysis of 16 patients who underwent wide resection of distal radius GCT and reconstruction with non-vascularized fibular graft from Feb 2016 to Feb 2024 was conducted. Patients were selected based on specific criteria, excluding recurrent cases. Ethical approval and informed consent were obtained, and standardized protocols were followed for evaluations, surgeries, and postoperative care. Functional outcomes, radiological assessments, and statistical analysis were performed using established tools and IBM SPSS Version 22.0. Results: The study included 16 patients (mean age: 40.9 years, 67% females), predominantly with Campanacci grade II tumors. The ipsilateral fibula was harvested in 66.7% of cases. The union rate was 93.3%, and the average time to union was 12.5 weeks. Functional outcomes showed preserved global range of motion (64%) and an average MSTS score of 78.4%. Complications included infected non-union, graft collapse, graft fracture, and iatrogenic common peroneal nerve injury. Recurrence rate was 18.75%, associated significantly with patient age. Conclusion: Reconstruction with ipsilateral non-vascularized fibular graft after en bloc resection emerges as a promising approach for distal radius GCT, offering favorable functional outcomes and an acceptable recurrence rate. The study emphasizes the importance of tumor grading, margin positivity, and fibuloulnar distance in predicting outcomes. The negative correlation between MSTS score and fibuloulnar distance calls for further investigation. The study encourages further exploration of statistical associations and reinforces the importance of surgical meticulousness in achieving optimal outcomes for patients with distal radius GCT.